Edukasi Pada Keluarga Tentang Perawatan Pasca Anestesi - Aswin Wikantama; Happy Nurhayati; Fira Early (Cakrawala: Jurnal Pengabdian Masyarakat Global, 2025)
Post-anesthesia care requires special attention to ensure optimal patient recovery and reduce the risk of complications. Families play a crucial role in providing support and monitoring patients after anesthesia. Proper education for families can enhance their understanding of post-anesthesia care, including vital signs monitoring, pain management, nutrition, and complication prevention. Adequate education helps families identify issues early and provide proper care, which, in turn, accelerates patient recovery. This study aims to evaluate the effectiveness of a family education program in improving their knowledge and readiness to care for post-anesthesia patients. The method used is a pre-test and post-test design with an intervention consisting of educational sessions that include presentations and interactive discussions. A pre-test was conducted before the educational session to assess the family’s initial knowledge regarding post-anesthesia care. After attending the educational session, a post-test was administered to measure the increase in their knowledge. The results of the study showed a significant increase in the family’s knowledge levels after attending the educational session. This program proved to be effective in enhancing the understanding and readiness of families to care for post-anesthesia patients. Therefore, this education program is recommended as part of standard healthcare services to improve the quality of post-anesthesia care and support faster and more effective patient recovery.